Decision Support Systems for Career Recommendations for Graduates in Islamic Broadcasting Communication Studies Using ANP and TOPSIS Methods - Alfiansyah, Raja; Zufria, Ilka (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
The insufficient number of alumni students displaying a strong work ethic can be attributed to a mismatch between the talents and interests of alumni in the UINSU MEDAN KPI area, which should be the focal point of monitoring for these Indonesian youths. The effective management of alumni can offer a potential solution. In this study, researchers employed the ANP method to calculate career recommendations and ranked them using the TOPSIS method. The research methodology included a comprehensive literature review, observational data collection, interviews, documentation analysis, system flowchart design, ANP method application, TOPSIS method application, and system testing conducted using the black box method. Based on the calculations using the ANP and TOPSIS methods, Alternative A1 emerged as the top priority, scoring 1, while Alternative A13 received the lowest priority with a score of 0.13. These calculations were based on six criteria: discipline, honesty, responsibility, teamwork skills, and technical or practical proficiency. The highest-ranked career recommendation was